(untitled) (SALAM Digest: Syariah and Law Undergraduate Symposium, 2023)
The right to citizenship has been recognizedsince the Universal Declaration of Human Rights in 1948. Children’s rights are expressly reinforced in several UN human rights accords and treaties. Statelessness, however, has grown to be a significant global problem with over 15 million people living without a nationality. State succession, technical and administrative shortcomings in the government, and discriminatory legislation are only a few of the factors that contribute to statelessness. From the standpoint of access to school, health benefits, access to property, and house ownership, this discriminatory citizenship law has had several detrimental effects on women and children. There are seven nations where women are not permitted to confer citizenship on their children, with few exceptions. This study focuses on Brunei and Kuwait, two of the seven nations where sufficient, accurate information is available. Citizenship discrimination creates a perception of children’s identities as primarily descended from the male line and considers women as second-class citizens, maintaining a sexist and discriminatory framework for women’s duties in the home and society. Therefore, this study evaluates the prevalence of statelessness as well as other detrimental effects on women and children as a result of gender-based disparity in citizenship legislation. The persons of concern database maintained by the United Nations High Commissioner for Refugees (UNHCR) is used for graphic analysis of statistics data in Brunei and Kuwait. Furthermore, for these two nations, a qualitative analysis is undertaken utilizing literature from the United Nations, the Institute on Statelessness and Inclusion, a case study, and other academic publications. Indeed, this study will also emphasize the current scenario of statelessness and other negative effects. In addition, this study recommends some proposed solutions or improvements that can be made by the governments of Brunei and Kuwait to address gender inequality in the legal system and societal ecosystem.